Exact values of mean $n$-widths for the classes of functions analytic in the upper half plane in the Hardy space - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
In the Hardy space $H_2 ℝ_+^2$ of functions analytic in the upper half plane such that$$\sup \left\{ {\int\limits_\mathbb{R} {|f(x + iy)|^2 dx: 0< y< ∞ } } \right\}< ∞ ,$$we determine mean $N$-widths and find their exact values for numerous classes of functions.